Personal health information system for tele-rehabilitation of stroke patients - Lim, Wei Jie Shang. (2012)
This report will cover the motivation and objectives of this project and the major benefits of using Tele-Medicine as a Tele-Rehabilitation feature for Stroke. The report will also look at Stroke as a whole and how is Singapore equipped to deal with it.